2016
DOI: 10.1162/jocn_a_00979
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing Working Memory Training with Transcranial Direct Current Stimulation

Abstract: Working memory (WM) is a fundamental cognitive ability that supports complex thought but is limited in capacity. Thus, WM training interventions have become very popular as a means of potentially improving WM-related skills. Another promising intervention that has gained increasing traction in recent years is transcranial direct current stimulation (tDCS), a noninvasive form of brain stimulation that can modulate cortical excitability and temporarily increase brain plasticity. As such, it has the potential to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
155
3
3

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 128 publications
(167 citation statements)
references
References 59 publications
6
155
3
3
Order By: Relevance
“…Prichard et al 2014). Furthermore, our previous work in the cognitive domain (Au et al 2016) showed similar effects using a WM intervention combined with online tDCS. As with motor skill, we also observed a higher rate of learning in our stimulated group, relative to sham.…”
Section: Experimental Evidencementioning
confidence: 58%
See 2 more Smart Citations
“…Prichard et al 2014). Furthermore, our previous work in the cognitive domain (Au et al 2016) showed similar effects using a WM intervention combined with online tDCS. As with motor skill, we also observed a higher rate of learning in our stimulated group, relative to sham.…”
Section: Experimental Evidencementioning
confidence: 58%
“…Moreover, our own work demonstrated with a WM intervention that participants showed the greatest improvement after a weekend break (Au et al 2016), suggesting in addition to the meta-plasticity protocols that longer spacing intervals of several days can actually be beneficial for consolidation as well. How do we reconcile these disparate results?…”
Section: Spacing Of Stimulationmentioning
confidence: 81%
See 1 more Smart Citation
“…A recent meta-analysis from Mancuso, Ilieva, Hamilton, and Farah (2016) suggests that dorsolateral pFC (DLPFC) stimulation during training results in a small but significant enhancement effect, which survives corrections for publication bias. Recent research from our own laboratory (Au et al, 2016) provides further evidence that DLPFC stimulation (both right and left) enhances performance on a widely used n-back training task over the course of seven sessions, relative to a sham stimulation condition. Although these initial findings do provide some preliminary support for the use of tDCS to enhance learning of WM-intensive tasks, we note considerable heterogeneity in the literature.…”
Section: Introductionmentioning
confidence: 90%
“…For example, a similarly designed n-back/ tDCS training study failed to find an effect of tDCS after correcting for baseline differences (Martin et al, 2013), and the 10 tDCS/ WM training studies covered in the Mancuso et al (2016) meta-analysis differ substantially in the magnitude of their effects, with Hedges' g values ranging from 0.074 to 0.565. A variety of factors, including differences in stimulation intensity, density, location, and other parameters, as well as the design and implementation of the cognitive training paradigm, may explain the disparities in the strength of these effects (see Au et al, 2016, for a brief discussion). However, one additional possibility is that individual differences among participants-including motivation, sex, and baseline ability, among many factors-may play important roles.…”
Section: Introductionmentioning
confidence: 99%